Pengaruh Budaya Organisasi, Worklife Balance Terhadap Kinerja Karyawan Pada Rumah Sakit Sinar Kasih Toraja - Diana Paembong; Adriana Madya Marampa; Rahma G. Tammu (Universitas Kristen Indonesia Toraja, 2023)
This study aims to determine the effect of organizational culture and work-life balance on the performance of employees at Sinar Kasih Toraja Hospital. The research method used in this research is descriptive quantitative research. The method of collecting data is by distributing questionnaires. .The sample in this study were 35 people. The data analysis technique used in this study was multiple regression testing with statistical calculation tools using SPSS version 25.0. The results of this study found that partially organizational culture has a significant effect on performance with a significant value of 0.005 <0.05 and a tcount value of 2.993> ttable 2.037.2, partially Work Life Balance has a significant effect on performance with a significant value of 0.011 <0.05 and a significant value of tcount 2.709 > ttable 2.037. Simultaneously organizational culture and work life balance simultaneously have a significant effect on the performance of Sinar Kasih Toraja Hospital employees with a significant value of 0.000<0.05 and fcount value 15.289>ftable 3.29.